Description of a new species of the genus Diastatotropis Lacordaire (Coleoptera: Anthribidae) with strikingly elongated elytral apices from north-eastern Madagascar - Trýzna, Miloš; Andrianomenjanahary, Mamy Nandrianina (Zootaxa, 2019)
A new species, Diastatotropis blazeji Trýzna sp. nov. (Anthribidae: Anthribinae: Cappadocini), from north-eastern Madagascar is described. Male and female genitalia are studied and illustrated and colour photographs are provided. It is distinguished from all species of the genus by the strikingly elongated apices of the elytra and the distinctly bright golden green colour of the upper side of the body.